Improved life cycle assessment for desalination : handling the choices and uncertainties - Zhou, Jin (2014)
A large number of choices are involved in desalination LCA studies. The aim of this study was to investigate how the choices influence the desalination LCA’s outcome, and further explore the approaches in order to capture the technique features and local context to improve the reliability of the results. This work investigated three choices which were considered as high-priority problems in LCA, including the choice of the system boundary, the choice of characterization approach, the choice of in-stock dataset as representative data for background characteristics. The critical review revealed the lack of consensus on the system boundary definition. Particular attention was given to three phases in foreground system of desalination LCAs, including infrastructure, chemical, and membrane phases. This work proposed to select their system boundaries according to the goal and scope. The advantage of proposed choice was to avoid large uncertainties due to the arbitrary and inconsistent choice. In addition, it also reduced the requirement of on-site primary data by identifying the significant elements in three phases. To examine the impacts by the choice of predefined life cycle impact assessment method on the result of desalination LCAs, a comparison study was carried out between a generic method and a regional specific method. The results indicated the choice do make a significant difference in the LCA characterization results of desalination. The divergences in the coverage level of different material flows, characterization models, and environmental interventions were identified as the major reasons. This study also provided some suggestions in choosing the appropriate predefined impact assessment method. Both generic method and regional specific method have merits and limitations in desalination applications. The choice should depend on the inventories’ availability and also the specific concerns in desalination technology and local environmental uniqueness. Singapore is still in the early stage of LCA, therefore the generic predefined impact assessment method is recommended for Singapore’s desalination LCAs. However, the generic method cannot capture the features of the brine disposal process. Therefore, an improved characterization approach, namely group-by-group approach was developed to estimate the aquatic eco-toxic impact of brine disposal. A comparison study was carried out between the proposed approach and the other two current approaches (chemical-by-chemical approach and whole effluent approach). The results indicated the improved approach reduces the reliance on the comprehensive chemical composition analysis and temporal ecotoxicology test of the complex desalination brine. It also provided a more comprehensive coverage, not only considering the impact of organic chemicals and metals, but also including the contribution of inorganic chemicals.